P5-S6.19 Prevalence and incidence of sexually transmitted infections among female sex workers in two cities in India: implications for STI control strategies. (10th July 2011) - Das, A; Prabhakar, P; Narayanan, P; Neilsen, G; Morineau, G; Mehendale, S; Risbud, A
Abstract : Background: India is a large country with marked heterogeneity in prevalence of sexually transmitted infections (STIs) which has implications for STI control strategies. The study objective was to measure the prevalence and incidence of common bacterial STIs in a cohort of female sex workers (FSWs) in known high STI prevalence cities in response to a package of standardised interventions under Avahan, the India AIDS Initiative of the Bill & Melinda Gates Foundation. Methods: FSWs attending clinics were followed up periodically over 6–9 months. At every visit, vaginal swabs were tested for Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) by Gen-Probe APTIMA Combo II. During the baseline and final visits, vaginal swabs were tested for Trichomonas vaginalis (TV) by PCR and blood was tested for syphilis using Rapid Plasma Reagin (RPR) with confirmatory Treponema pallidum Haemagglutination Assay (TPHA). All participants received presumptive treatment for gonorrhoea and chlamydia at the baseline visit and syndromic STI management at all subsequent visits. Results: A total of 417 FSWs were recruited, 360 returned for at least one follow-up visit, and 282 completed the final visit. The total follow-up period was 109.4 person years (median 0.18 years, maximum 1.07 years). Self-reported consistent condom use with commercial and regular partners was 70% and 17%, respectively. A substantial proportion of cervical and trichomonal infections were asymptomatic (see Abstract P5-S6.19 table 1 ). The incidence of GC/CT and TV was 1.0 and 2.0 per person year respectively. Three new cases of latent syphilis were detected at the final visit. Conclusions: The incidence of GC, CT and TV and the considerable burden of asymptomatic infections indicate the need for periodic presumptive treatment at high STI prevalence sites in India. The current regime of bi-annual syphilis screening is justified. Consistent condom use and partner treatment, particularly for regular partners, need to be re-emphasised.